Systemic identification and characterization of the conserved core NuRD complex in planarian - Huang, Lei; Wang, Hao; Wu, Shuang; Chai, Jiangnan; Zou, Xiaopeng; Liu, Hongfei; Guo, Zhengwei; Wang, Yanming; Kan, Yunchao (Frontiers in Aging, 2025)
The nucleosome remodeling and deacetylase (NuRD) complex, well known for its ATP-dependent chromatin remodeling and histone deacetylation activities combined in one multi-subunit complex, plays an evolutionarily conserved role in chromatin structures and gene regulation during cell growth, proliferation, and development. However, the composition and function of the NuRD complex in planarians remain incompletely unknown. Here, we identified six core components within the NuRD complex and characterized their biological roles in planarians. RNA interference (RNAi) mediated knockdown of these genes resulted in similar perturbations to both tissue homeostasis and regeneration, and the overlapping downstream genes regulated upon depletion of MBD2/3 or CHD4 showed similar expression alterations to that after knockdown of other NuRD complex genes, suggesting that NuRD core members may act in one complex. Additionally, the overlapping upregulated genes after depletion of NuRD complex members were expressed in neoblast and progenitor cells, among which NuRD complex core genes were enriched, suggesting transcriptional correlation between the overlapping upregulated genes and NuRD core members. Furthermore, upstream regulatory sites of the upregulated genes exhibited significant enrichment of H3K27ac, indicating the NuRD complex may deacetylate histone to modulate these genes. Notably, depletion of either MBD2/3 or CHD4 in planarians significantly upregulated multiple progenitor marker genes while reducing the number of somatic cells in the epidermis and intestine and downregulating multiple somatic cell marker genes, indicating that the NuRD complex may drive differentiation into somatic lineages in planarians. Collectively, our work provides a foundation to understand the essential roles of the NuRD complex in orchestrating cell differentiation, tissue homeostasis and regeneration in planarian.